Women with pre‐gestational diabetes have a higher risk of stillbirth at all gestations after 32 weeks. Issue 9 (2nd June 2014) - Holman, N.; Bell, R.; Murphy, H.; Maresh, M.
Abstract Aim To explore the additional risk of stillbirths and to quantify that risk according to gestational age among women with diabetes. Methods Data on pregnancies ending in 2007 and 2008 in women with pre‐gestational diabetes in three English regional audits were identified. A prospective audit collected data on all pregnancies delivering between June 2010 and May 2011 in one region and in 13 other units across England. The data on all singleton pregnancies from these two cohorts were combined. Comparisons were made to all births in England and Wales for the same time period using data from the Office for National Statistics. Results In the cohort of women with pre‐gestational diabetes there were a total of 2085 singleton pregnancies, of which 29 resulted in a stillbirth (overall stillbirth rate 13.9 per 1000, 95% CI 9.7–19.9, relative risk compared with all pregnancies in England and Wales 2.73, 95% CI 2.61–2.84). The relative risk of stillbirth between 32 and 34 weeks' gestation was 4.95 (95% CI 4.24–5.78), 3.77 (95% CI 3.42–4.16) at 35 to 36 weeks, 5.75 (95% CI 5.43–6.09) for deliveries at 37 or 38 weeks and 7.34 (95% CI 6.52–8.25) for those born at 39 weeks or more. Conclusion Women with diabetes have a significantly higher risk of stillbirth at all gestations after 32 weeks and this additional risk is not just confined to pregnancies at 37 weeks or more.